How is students’ mental model in the post-pandemic era? Work and Energy Concept Analysis using the Wright Map - Fanny Herliyana Dewi; Achmad Samsudin; Didi Teguh Chandra; Adam Hadiana Aminudin; Jajang Kunaedi; Itsna Rona Wahyu Astuti; Fini Alfionita Umar; Shobrina Nurul Mufida (Postgraduate, University of Mataram, 2023)
Students' mental models are important to be analyzed properly. Mental models are able to be described for students’ knowledge and diagnosed students’ learning difficulties. This study aims to analyze students' mental models on work and energy concept in the post-pandemic covid-19 era. Students' mental models were measured by four-tier test instrument and analyzed using the wright map. The research study utilizes descriptive-quantitative research method. The participant of this study are 31 K-10 students (13 boys and 18 girls) at high school in the West Java, Indonesia. The data analysis shows that the most student had category of in (51.52%), Sy-D (18.52%), furthermore caterogy Sy-C (13.52%), Sy-B (11.29%), and only less students that had category of Sy-A (2.95%) and Sc (2.2%). It could be concluded that physics learning in forming students' mental models needs to be improvised immediately.